Learning the Value of Character Education from Indonesian Animation Series: Adit & Sopo Jarwo - Nurmala, Viviani; Sujarwo; Lidyasari, Aprilia Tina; Nugroho, Ikhlasul Ardi; Adi, Banu Setyo; Kawuryan, Sekar Purbarini (Indonesian Journal of Educational Research and Review, 2024)
It is urgent to carry out character education because with the provision of character education students will be able to empower their potential to build their personal character so that they are able to become individuals who are beneficial to themselves and their environment. Focus and aim of this research is to analyze the value of character education from the Indonesian Animation Series: Adit Sopo Jarwo for elementary school students. Type of research used is a qualitative research method with a descriptive type. The data sampling technique used purposive sampling and the samples in this study were  fourth grade elementary school students and teachers who taught in that class. The research procedure used in this research uses qualitative data analysis techniques, namely data collection, data reduction, presenting data in descriptive form and making conclusions. Data collection techniques were carried out using interviews and observations. Based on the research that has been carried out, the results and conclusions are obtained that the Indonesian Animation series Adit & Sopo Jarwo has character education value, namely the mutual cooperation character in the episode "Serunya Kerja Bakti dan Tamasya Bersama" and the independent character in the episode "Bunda Pergi Adel Mandiri", so that the Indonesian Animation series Adit & Sopo Jarwo can be used as audio visual media to instill the character of mutual cooperation and independence in elementary school students.